The learning curve how business schools are re-inventing education - Iñiguez de Onzoño, Santiago (Houndmills, Basingstoke, Hampshire ; New York Palgrave Macmillan, 2011)
"How do you create world-class educational institutions that are academically rigorous and vocationally relevant? Are business schools the blueprint for institutions of the future, oran educational experiment gone wrong?This is thefirst title in a new series from IE Business School,IE Business Publishing"-- Provided by publisher.
Part I. The Trailblazers: 1. Why management matters; 2. Out of the crisis, confronting the critics; 3. Developing better managers -- Part II. Today?s Pressing Challenges: 4. The changing landscape; 5. E-Learning; 6. International stakeholders; 7. Melting pots of knowledge -- Part III. The Next Learning Curve: 8. The purpose of business schools; 9. The students of tomorrow; 10. Faculty and knowledge creation: how does it work?
Keywords: Business education; Business schools; Management -- Study and teaching